2020
DOI: 10.1002/macp.202000263
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerize Conventional Vinyl Monomers to Degradable and Water‐Soluble Copolymers with a Fluorescence Property

Abstract: In the copolymerization of acrylamide (Am) and hydroxyethyl acrylate (HEA), the initial product is a carbon chain polymer with hydroxyl and amide side groups. However, in the present work, these two conventional vinyl monomers are combined into a degradable heterochain copolymer by using a phosphazene base, t‐BuP4, as a catalyst. NMR not only confirms that the backbone of the resulting copolymer is composed of ester–ether units and amide units but also suggests that the resulted secondary amide group retains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…To seek a solution, we characterized in detail the polymer (PHEA-1, in Table 1) obtained from HTP of HEA according to our previous work by using a phosphate catalyst, t-BuP 2 . 21,27 The weight-average molecular weight of the resultant polymer HEA was first catalyzed by t-BuP 2 , and then BDDA with t-BuP 4 was added to the system at a fixed time. b The polymerization temperature was first set at −5 °C for 12 h and then increased to 80 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To seek a solution, we characterized in detail the polymer (PHEA-1, in Table 1) obtained from HTP of HEA according to our previous work by using a phosphate catalyst, t-BuP 2 . 21,27 The weight-average molecular weight of the resultant polymer HEA was first catalyzed by t-BuP 2 , and then BDDA with t-BuP 4 was added to the system at a fixed time. b The polymerization temperature was first set at −5 °C for 12 h and then increased to 80 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…26 Our previous work also suggested that hydrogen transfer copolymerization (HTcoP) could produce a degradable heterochain copolymer with a high selectivity and sensitivity for Ba 2+ , Fe 2+ , and Fe 3+ cations. 21,27 A milestone work in this area was achieved in 2016 by Chen et al, who found that N-heterocyclic carbenes could catalyze the HTP of dimethacrylate to an unsaturated polyester. 28 This work departed from both the typical HTP processes and traditional acrylic polymerization systems.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a continuously growing interest in developing nonconventional aliphatic macromolecular luminogens for diverse applications. [1][2][3][4][5][6] Notably, the conventional conjugated fluorescent polymers as well as aromatic probes are more susceptible toward photobleaching than those of aliphatic macromolecular sensors. [7] The cytotoxicity, small Stokes' shift, lack of durability, and self-quenching of conventional fluorescent polymers make these luminogens less attractive for diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NTIL compounds may exhibit some unique features in the process of phase change. Unfortunately, although a lot of amine‐containing NTIL compounds including small molecules, oligomers, and polymers have been reported to possess remarkable fluorescence, [ 17–26 ] most of them were conducted in solution, and a few works in solid state. [ 9,27–29 ] Especially, a systematic research on the fluorescence variation from solution through gel to solid state has not been investigated.…”
Section: Introductionmentioning
confidence: 99%